Denkbeeldige Wereld: The New Dutch Guidelines for Economic Evaluations in Healthcare - Paul C Langley (University of Minnesota Libraries Publishing, 2017)
In 2016 the Dutch National Health Care Institute (Zorginstituut Nederland) published a new guidance for economic evaluations in healthcare to support reimbursement decisions. These Guidelines update and replace three previously published guidelines covering pharmacoeconomic evaluation, outcomes research and costing. The purpose of this commentary is to consider the merits of these new Guidelines from the perspective of modeled claims which meet the standards of normal science: credibility, evaluation and replication in the treatment of target patient populations. In evaluating the merits of the Guidelines the focus will be on the requirement for submissions to follow reference case standards where lifetime-cost-per-QALY claims are the preferred outcome measure. The assessment points out that in adhering to a reference case standard, the Dutch Guidelines, in common with those in the UK, Ireland and New Zealand, fail to address the fundamental question of claims assessment. Rather, in relying upon the reference case imaginary world (denkbeeldige wereld) to inform decision makers, the possibility of evaluating claims and generating feedback to decision makers on comparative effectiveness is put to one side. We have no idea as to whether the claims are right or even if they are wrong. Hopefully, future versions of the guidelines will address this issue and focus on a rigorous program of claims assessment.   Type: Commentary